2015
DOI: 10.3141/2520-04
|View full text |Cite
|
Sign up to set email alerts
|

When Do Drivers Yield to Cyclists at Unsignalized Roundabouts?

Abstract: Cycling popularity has shown an increasing trend during the last decades in many cities of Europe and USA because of its environmental and health benefits. However, cyclists are frequently involved in traffic accidents, especially, when they interact with vehicles at unsignalized intersections. There is still lack of evidence and analysis on how such interaction is performed. This paper explores empirical evidence of the vehicle-bicycle interaction on a typical Swedish roundabout, and provides insights into fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…If a driver's approach speed is higher, their yielding behaviour towards cyclists' decreases. Silvano et al (2015) conversely suggested that cyclist speed has a slight effect on vehicle yielding behaviour. while any increase in vehicle speed causes a sharp decrease in the yielding probability.…”
Section: A Critical State Of the Art Review For Cyclist Safety At Roundaboutsmentioning
confidence: 99%
See 3 more Smart Citations
“…If a driver's approach speed is higher, their yielding behaviour towards cyclists' decreases. Silvano et al (2015) conversely suggested that cyclist speed has a slight effect on vehicle yielding behaviour. while any increase in vehicle speed causes a sharp decrease in the yielding probability.…”
Section: A Critical State Of the Art Review For Cyclist Safety At Roundaboutsmentioning
confidence: 99%
“…Previous research has been critically reviewed to endorse the research gaps identified and to inform which variables have been found to be important and therefore need to be considered in this research, the results of which are presented later sections of this manuscript. Studies (Rasanen and Summala, 2000;Silvano et al, 2015) claimed that the possible major factors related to cyclist-vehicle collisions might be driver behaviour and yielding problems. 7-15% of drivers were found not to be aware of cyclists approaching from the right (Rasanen and Summala, 2000).…”
Section: A Critical State Of the Art Review For Cyclist Safety At Roundaboutsmentioning
confidence: 99%
See 2 more Smart Citations
“…Wood et al [10] found that drivers' attitudes regarding bicycle visibility disagree with those of bicyclists, which also causes the V-B accidents. Silvano et al [11] found that drivers would yield to bicyclists in V-B conflicts at unsignalized roundabouts. Though these researches investigated drivers' behaviors in V-B conflicts, they provided no specific profile of drivers' braking behaviors.…”
Section: Introductionmentioning
confidence: 99%